c-Myc-Induced Survivin Is Essential for Promoting the Notch-Dependent T Cell Differentiation from Hematopoietic Stem Cells - Haque, Rizwanul (Genes (Basel), 2017)
Notch is indispensable for T cell lineage commitment, and is needed for thymocyte differentiation at early phases. During early stages of T cell development, active Notch prevents other lineage potentials including B cell lineage and myeloid cell (e.g., dendritic cell) lineage. Nevertheless, the precise intracellular signaling pathways by which Notch promotes T cell differentiation remain unclear. Here we report that the transcription factor c-Myc is a key mediator of the Notch signaling–regulated T cell differentiation. In a well-established in vitro differentiation model of T lymphocytes from hematopoietic stem cells, we showed that Notch1 and 4 directly promoted c-Myc expression; dominant-negative (DN) c-Myc inhibited early T cell differentiation. Moreover, the c-Myc expression activated by Notch signaling increased the expression of survivin, an inhibitor of apoptosis (IAP) protein. We further demonstrated that over-expression of c-Myc increased the abundance of survivin and the T cell differentiation thereof, whereas dn c-Myc reduced survivin levels and concomitantly retarded the differentiation. The c-Myc–dependent survivin induction is functionally germane, because Notch-dependent T cell differentiation was canceled by the depletion of survivin. These results identify both c-Myc and survivin as important mediators of the Notch signaling–regulated differentiation of T lymphocytes from hematopoietic stem cells.